Persistent luminescent multifunctional drug delivery nano-platform based on nanomaterial ZnGa2O4:Cr3+, Sn4+ for imaging-guided cancer chemotherapy. Issue 18 (11th April 2019) - Jiang, Wenjing; Huang, Lin; Mo, Fan; Zhong, Yingying; Xu, Liangjun; Fu, FengFu
Abstract : A novel tumor-targeting and release-controllable drug delivery nano-platform with persistent luminescence was constructed for imaging-guided cancer chemotherapy based on the ZnGa2 O4 :Cr 3+, Sn 4+ (ZGCS) nanoparticles. Abstract : A novel tumor-targeting and release-controllable drug delivery nano-platform with persistent luminescence was constructed for imaging-guided cancer chemotherapy. The persistent luminescent drug delivery nano-platform employed the persistent luminescent nanoparticles ZnGa2 O4 :Cr 3+, Sn 4+ (ZGCS) to realize the repeatable luminescence imaging of cells or tissues with high signal-to-noise ratio. Mesoporous silica (MS) was coated on the ZGCS surface to load drugs, and hyaluronic acid (HA) acted as gatekeeper and targeting moiety. The proposed nano-platform could repeatedly be excited to produce persistent luminescence under red light (550 nm) irradiation to realize repeatable luminescence imaging of cells or tissues without in situ excitation, and simultaneously possessed an excellent tumor-targeting ability towards CD-44 over-expressing cancer cells and controllable drug release with hyaluronic acidase (Hyal-1) response. By using the nano-platform, we have successfully delivered the non-fluorescent chemotherapeutic drug, paclitaxel (Ptx), into human breast adenocarcinoma cells (MCF-7 cells) with a loading capacity of 0.187 mg mg −1 and Hyal-1 responsive controllable-release, and simultaneously, we monitored the distribution of the nano-platform and the release of Ptx in target cells by luminescence-imaging. The combination of excellent persistent luminescence feature, tumor-targeting ability and controllable drug release makes this nano-platform a promising tool for imaging-guided cancer chemotherapy, which will greatly enhance the chemotherapeutic efficiency of the drug and reduce the side effects.